Information access, governance support and operational flexibility are needed to drive adaptation of European forests to global change - Willig, Julius; Häublein, Sabeth; Sorge, Stefan; Brudermann, Annechien; Cantarello, Elena; Espelta, Josep Maria; Häyrinen, Liina; Hlasny, Tomás; Horstmann, Nina; Krajter Ostoić, Silvija; Lautrup, Marie; Ostrogović Sever, Maša Zorana; et al. (Elsevier, 2025)
Many forest owners and professionals recognize global change and increasing forest disturbances as pressing challenges but have yet to implement adaptation options to counteract the impacts on their forests. The ecological effectiveness of these options is context-dependent, influenced by site conditions and the quality of implementation. In addition, the socio-economic context can support or impede the implementation of adaptation options. To assess the relevance of implementation barriers and how they are perceived, we surveyed over 800 forest owners and professionals across Europe. Adaptation options that were perceived as effective were also more likely to be applied. Owing to its low evidence of effectiveness and conflicts with other management objectives, non-management was largely regarded as a non-viable adaptation option. Overall, respondents rated the importance of most implementation barriers as low to moderate. However, for certain adaptation options, specific barriers were perceived as particularly relevant. Forest owners and professionals with experience in practicing forest adaptation regarded potential barriers as less constraining than other groups of participants. More timber production-oriented owners and professionals identified economic issues as particularly constraining. To facilitate implementation of adaptation, participants suggested improved communication, more education, more flexible legislation and simpler access to financial support. Different specific site and management contexts complicate the development of general recommendations. Therefore, local science-practice collaborations and platforms to share experiences regarding adaptation options could promote the adaptive capacity of forest owners and professionals.
Keywords: climate change adaptation; silvicultural management options; adaptation barriers and enablers; cluster analysis; social-ecological system